2000
DOI: 10.1001/archinte.160.20.3074
|View full text |Cite
|
Sign up to set email alerts
|

Six-Year Effect of Depressive Symptoms on the Course of Physical Disability in Community-Living Older Adults

Abstract: Mild depressive symptoms in older persons (those aged > or =65 years) are associated with an increased likelihood of becoming disabled and a decreased chance of recovery, regardless of age, sex, and other factors that contribute to physical disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
112
0
13

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(133 citation statements)
references
References 41 publications
8
112
0
13
Order By: Relevance
“…Depressed cynomolgus macaques share many physiological, neurobiological, and behavioral characteristics of human depression, including reduced body mass, hypothalamic-pituitary-adrenal axis perturbations, autonomic dysfunction, increased cardiovascular disease risk, reduced hippocampal volume, altered serotonergic function, decreased activity levels, low ovarian steroid levels, and increased mortality (Shively et al 2008(Shively et al , 2017Willard and Shively 2012;Willard et al 2015;Silverstein-Metzler et al 2017;. In this investigation, we also confirm the susceptibility of depressed monkeys to exhibit functional declines and increased sedentariness as observed clinically at mid to late life (Bromberger and di Scalea 2009;Lenze et al 2005;Cronin-Stubbs et al 2000). Second, the study benefited from measurement of multiple conceptually related but independent outcomes related to function, activity, and sedentariness.…”
Section: Sedentary Behaviorsupporting
confidence: 76%
“…Depressed cynomolgus macaques share many physiological, neurobiological, and behavioral characteristics of human depression, including reduced body mass, hypothalamic-pituitary-adrenal axis perturbations, autonomic dysfunction, increased cardiovascular disease risk, reduced hippocampal volume, altered serotonergic function, decreased activity levels, low ovarian steroid levels, and increased mortality (Shively et al 2008(Shively et al , 2017Willard and Shively 2012;Willard et al 2015;Silverstein-Metzler et al 2017;. In this investigation, we also confirm the susceptibility of depressed monkeys to exhibit functional declines and increased sedentariness as observed clinically at mid to late life (Bromberger and di Scalea 2009;Lenze et al 2005;Cronin-Stubbs et al 2000). Second, the study benefited from measurement of multiple conceptually related but independent outcomes related to function, activity, and sedentariness.…”
Section: Sedentary Behaviorsupporting
confidence: 76%
“…Von Korff and Simon concluded that chronic pain and depression are inter-related problems with pain contributing to depression and vice versa (Von Korff and Simon, 1996). Several reports have shown that depression is a contributor to disability (Bruce et al, 1994;Penninx et al, 1998Penninx et al, , 1999Cronin-Stubbs et al, 2000) and, though less well-studied, anxiety symptoms have been found to modestly predict worsening disability in the WHAS. The role of analgesics, often underused in management of pain in older adults, has rarely been addressed but may contribute to maintenance of function.…”
Section: Introductionmentioning
confidence: 99%
“…However, depressive disorders could lead to cognitive difficulties and may predict cognitive dysfunction 19) . Some previous studies have shown a correlation between cognitive dysfunction or depressive symptoms and decline in physical functioning 20) . However, other studies found no relationship between cognitive dysfunction and depressive disorders.…”
Section: Discussionmentioning
confidence: 99%